The effects of replacing soybean meal with dried distiller's grain and corn gluten feed on Boer-type grower rations - Edington, Jordan E.; Crane, Alison R.; Lattimer, James M.; Jones, Cassandra K. (My University, 2019)
Evaluating different Boer goat grower rations is important in being cost effective with goat growth and performance. There have been few research experiments done on goat growth. The objective of this experiment was to evaluate the effects of replacing SBM with varying levels of DDGS and CGF. There were 75 Boer- type goats that were approximately 70 d of age. There were 3 goats per pen and 5 pens per treatment. Goats were randomly assigned treatments and pens, and the experimental unit was the pen. The alpha value was 0.05, and the data was analyzed using GLIMMIX in SAS (v. 9.4, Cary, NC). The treatments were: 1) SBM; 2) 100% DDGS/0% CGF; 3) 66% DDGS/33% CGF; 4) 33% DDGS/66% CGF; 5) 0% DDGS/100% CGF. The treatments varied in protein sources however they were all isocaloric and isonitrogenous. The linear P value of ADG was 0.444, ADFI was 0.371, and G: F was 0.442, and this concludes that there were no detectable differences among treatments for ADG, ADFI, and G: F (P>0.05). The feed cost per goat for this experiment for the SBM was $8.89, 100% DDGS/0% $7.96, 66% DDGS/33% CFG $7.26, 33% DDGS/66% CFG $7.54, and 0% DDGS/100% CFG was $7.80. Feed cost per pound of gain for each treatment groups are as followed: SBM $0.77, 100% DDGS/0% CFG $0.74, 66% DDGS/33% CFG $0.79, 33% DDGS/66% CFG $0.81, and 0% DDGS/100% CFG $0.86. The feed cost per pound of feed for the control was $0.11, and for treatments 1,2,3, and 4 it was $0.09. This project concludes that DDGS and CGF can utilized as replacements for SBM in grower rations for Boer goats.
Keywords: Spring 2019